2019
DOI: 10.1029/2019jc015206
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Resonance and Spatial Pattern of Natural Oscillation Modes With Multiple Resonators

Abstract: Tsunami resonance and coupled oscillation of shelf and bays modes has been reported to be important in tsunami wave amplification. The main objective of this work is to study the spatial pattern of natural oscillation modes and to analyze the influence of several resonators on the coast of the central Chile, which has a complex morphology with several bays, submarine canyons, and a wide continental shelf. First, natural oscillation modes were computed by means of modal analysis of local and regional domains. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…The sea-level records of the 2014 Pisagua and the 2015 Illapel earthquakes were extracted from the coastal tide-gauge network [ http://www.ioc-sealevelmonitoring.org ]. The tsunami records were processed through a zero-phase digital high-pass filter to eliminate signals over a 3-h period to filter out tidal variations 76 . This value is selected based on the results of Bai et al 77 , thus only shelf and bay modes may be identified.…”
Section: Methods and Datamentioning
confidence: 99%
“…The sea-level records of the 2014 Pisagua and the 2015 Illapel earthquakes were extracted from the coastal tide-gauge network [ http://www.ioc-sealevelmonitoring.org ]. The tsunami records were processed through a zero-phase digital high-pass filter to eliminate signals over a 3-h period to filter out tidal variations 76 . This value is selected based on the results of Bai et al 77 , thus only shelf and bay modes may be identified.…”
Section: Methods and Datamentioning
confidence: 99%
“…For the much smaller Mw 6.8 Zemmouri-Boumerdes event in the Mediterranean, we observed an opposite tendency towards underestimation. A possible reason is that, for smaller earthquakes on steeper faults like this, local resonances and amplification play a more important relative role due poorly modelled smaller tsunami wavelengths; for the Mw 8.8 Maule event, shelf and basin resonances occur also at longer periods 101 , but they are well-captured on a 30 arc-sec grid (see Methods).…”
Section: Ptf For the 2003 Mw 68 Zemmouri-boumerdes Earthquakementioning
confidence: 99%
“…It does not restrict the wavelengths and can produce modes composed of both stationary and progressive waves. For more details about the mathematical principles of this method, refer to the work of Cortés et al (2017) and Aránguiz et al (2019).…”
Section: Modal Analysismentioning
confidence: 99%